Protective Role of Glutathione and Nitric Oxide Production in the Pathogenesis of Pterygium - Fidelina Parra; Alexander Kormanovski; Gustavo Guevara-Balcazar; María del Carmen Castillo-Hernández; Antonio Franco-Vadillo; Mireille Toledo-Blas; Rosa Adriana Jarillo-Luna; Eleazar Lara-Padilla (Journal of Ophthalmology)
Objective. In the pathogenesis of pterygium, the protective role of glutathione and nitric oxide production is unclear. These are important factors for homeostasis in the redox state of cells. The aim of this study was to determine the levels of these and related parameters in pterygium tissue. Patients and Methods. The study sample consisted of 120 patients diagnosed with primary or recurrent pterygium. Five groups of tissue samples were examined: control, primary pterygium, recurrent pterygium, and two groups of primary pterygium given a one-month NAC presurgery treatment (topical or systemic). The levels of endothelial nitric oxide synthase (eNOS), nitric oxide (NO), 3-nitrotyrosine (3NT), reduced and oxidized glutathione (GSH and GSSG), and catalase (CAT) were evaluated in tissue homogenates. Results. Compared with the control, decreased levels of eNOS, NO, and 3-nitrotyrosine as well as the degree of oxidation of GSH (GSSG%) were observed in primary and recurrent pterygium. 3-Nitrotyrosine and GSSG% were reduced in the other pterygium groups. GSH and CAT were enhanced in recurrent pterygium and systemic-treated primary pterygium but were unchanged for topical-treated primary pterygium. There was a strong positive correlation of eNOS with NO and 3NT, GSSG% with NO and 3NT, and GSH with GSSG and CAT. Women showed a higher level of GSH and catalase in primary pterygium, whereas a lower level of GSH and a higher level of NO in recurrent pterygium. Conclusion. The results are congruent with the following proposed sequence of events leading to a protective response of the organism during the pathogenesis of primary pterygium: a decreased level of eNOS provokes a decline in the level of NO in pterygium tissue, which then leads to reduced S-nitrosylation of GSH or other thiols and possibly to the modulation of the intracellular level of GSH through synthesis and/or mobilization from other tissues.